Inland populations of sugar maple manifest higher phenological plasticity than coastal populations - Zhou, Yongzhi; Bai, Chunmei; Guo, Xiali; Mohytych, Vasyl; Klisz, Marcin; Delagrange, Sylvain; Rossi, Sergio (Frontiers in Ecology and Evolution, 2023)
Plasticity is vital for plants to rapidly acclimate to environmental changes, especially under the climate change pressure. However, while advancing bud break and disrupting plant phenology with the local climate, global warming also heightens the risk of frost damage to developing leaves. In this study, we explored the phenological plasticity of bud burst among populations of half-sib family sugar maple (Acer saccharum Marsh.) seedlings from 11 seed origins in two common gardens located close and at the Northern limits of the species distribution in Quebec, Canada. Results showed that the phenological plasticity of trees originating from inland was significantly higher than those from coastal areas at the beginning of leaf development. This discrepancy may result from differences in spring climate between seed origins. In the inland, seedlings evolved with a more extensive interannual range of spring temperature than the coast, where spring climate is more buffered by oceanic influence. Our study suggests that in the context of climate warming, the higher plasticity observed in sugar maple originating from inland areas may benefit from the phenological adaptation of sugar maple and the survival of local populations. It also suggests that inland populations may have a higher potential for use in assisted migration efforts, but this needs to be confirmed for other performance traits than spring phenology.